2017
DOI: 10.3390/nu9080907
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Targeted Molecular Effects of Hibiscus sabdariffa Polyphenols: An Opportunity for a Global Approach to Obesity

Abstract: Improper diet can alter gene expression by breaking the energy balance equation and changing metabolic and oxidative stress biomarkers, which can result in the development of obesity-related metabolic disorders. The pleiotropic effects of dietary plant polyphenols are capable of counteracting by modulating different key molecular targets at the cell, as well as through epigenetic modifications. Hibiscus sabdariffa (HS)-derived polyphenols are known to ameliorate various obesity-related conditions. Recent evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 118 publications
(179 reference statements)
2
44
1
2
Order By: Relevance
“…Considering the accumulated evidence on the effects of plant-derived polyphenols on obesity models, we proposed that some specifically designed nutraceuticals based on polyphenolic extracts may offer additional support for these particular patients in the management of obesity. 17,20,23 Over the years, scientific evidence has shown that polyphenolic extracts from plant sources may be valuable tools to treat obesity. 24 In this regard, our research at the pre-clinical and clinical level has shown the efficiency of the polyphenolic extracts from LC and HS.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the accumulated evidence on the effects of plant-derived polyphenols on obesity models, we proposed that some specifically designed nutraceuticals based on polyphenolic extracts may offer additional support for these particular patients in the management of obesity. 17,20,23 Over the years, scientific evidence has shown that polyphenolic extracts from plant sources may be valuable tools to treat obesity. 24 In this regard, our research at the pre-clinical and clinical level has shown the efficiency of the polyphenolic extracts from LC and HS.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Recent in vitro studies suggest that polyphenolic extracts from Lippia citriodora (LC) and Hibiscus sabdariffa (HS) reduce intracellular lipid accumulation and decrease high glucose-induced oxidative stress and inflammation in adipose tissue through the regulation of different metabolic pathways. [12][13][14][15][16][17] The accumulated evidence suggests that a multi-targeted mechanism (regulation of signaling and energy-sensitive pathways, oxidative stress and inflammation-related processes, mitochondrial functionality and membrane-dependent processes) is involved rather than the simple modulation of oxidative stress. [17][18][19][20] Most of these effects have been corroborated in hyperlipidemic animal models in which the continuous consumption of these polyphenolic extracts prevented fatty liver disease and improved lipid metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…In Sudan, the leaves of roselle are consumed as either a fresh or dried vegetable that is cooked with onion and groundnuts [13] Roselle leaves are consumed as a vegetable in Malaysia and Nigeria, [13,14] where they are also used for making jam because of their high pectin content. [15] Its brilliant red petals are usually processed into unique and refreshing alcoholic and non-alcoholic drinks. [16] The extracts from roselle calyces are consumed across the world as either a cold beverage or a hot drink.…”
Section: Introductionmentioning
confidence: 99%
“…In ancient times, H. sabdariffa was mainly used for treating inflammatory, neurological, and cardiac diseases (Da‐Costa‐Rocha, Bonnlaender, Sievers, Pischel, & Heinrich, ). In recent years, numerous experimental studies have confirmed its exact pharmacological effects in regulating blood lipids among subjects with metabolic disorders, which may be closely associated with its antioxidant and anti‐inflammatory activities, as well as the regulatory role in energy metabolism and hormone secretion (Herranz‐Lopez et al, ). Accumulating evidence suggests that polyphenols, polysaccharides, anthocyanins, and other bioactive constituents contained in it maybe the material basis of the multipathway therapeutic effects (Da‐Costa‐Rocha et al, ).…”
Section: Introductionmentioning
confidence: 97%